1997
DOI: 10.1093/ije/26.2.349
|View full text |Cite
|
Sign up to set email alerts
|

Association of breastfeeding and stunting in Peruvian toddlers: an example of reverse causality

Abstract: The negative association between breastfeeding and linear growth reflected reverse causality. Increased breastfeeding did not lead to poor growth; children's poor growth and health led to increased breastfeeding. Children's health must be considered when evaluating the association of breastfeeding with anthropometric outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
3
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(101 citation statements)
references
References 16 publications
9
87
3
2
Order By: Relevance
“…We believe however that the fact that breastfeeding was associated with LAZ but not in the direction of a better practice translating into better LAZ ( þ 0.16 z-score in favour of non-breast-fed infants) can partly explain why the ICFI does not relate to LAZ. Although this is not specific to urban contexts, it has been shown that mothers sometimes may prolong breastfeeding for stunted children (Marquis et al, 1997;Simondon and Simondon, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…We believe however that the fact that breastfeeding was associated with LAZ but not in the direction of a better practice translating into better LAZ ( þ 0.16 z-score in favour of non-breast-fed infants) can partly explain why the ICFI does not relate to LAZ. Although this is not specific to urban contexts, it has been shown that mothers sometimes may prolong breastfeeding for stunted children (Marquis et al, 1997;Simondon and Simondon, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…Outros autores [26][27][28] explicam o mesmo processo como tendo causalidade reversa, ou seja, os déficits no crescimento infantil levariam a mudanças nos padrões de alimentação, o que favoreceria a complementação ou cessação anterior da amamentação.…”
Section: Discussionunclassified
“…intake of nutritional and nutritious foods will affect the child's condition at the age of the child. [18,21] …”
Section: Methodsmentioning
confidence: 99%
“…The Breast is not a risk factor for stunting events in infants [18]. As it is known that the function of breast milk that is as an anti-infection that can affect stunting status changes in infants and also the length of breastfeeding is lacking and feeding or formula milk too early may increase infections such as diarrhea and ISPA [17].…”
Section: Exclusive Breastfeedingmentioning
confidence: 99%